Evaluasi Penerapan Protokol Kesehatan Di Kampung Tangguh Semeru Perumahan Mastrip Kabupaten Jember - Fariha Mariroh; Ari Rizki Racheshi; Endah Putri; Nonik Aisyah Rohman; Weni Widiyasari; Isa Ma’rufi (Multidisciplinary Journal, 2020)
Corona virus is a new variety of virus which shocks the world for its infections on millions of people all over the world in just a short period of time. Indonesian Government has put its greatest effort to deal with COVID19 by Kampung Tangguh Semeru (SEMERU RESILIENT KAMPONG). One of Kampung Tangguh Semeru in Jember Regency is Perumahan Mastrip RW 18-21 Kecamatan Sumbersari. High level of solidarity and communal mutual cooperation has made the area as the pilot area for COVID19 countermeasures. This research has purpose to evaluate the implementation of health protocol in the piloted residential area. Qualitative and descriptive analytic approach is employed during the research. The findings indicate that health protocol has been implemented well in SEMERU TOUGH KAMPONG Mastrip Residence. The good implementation of indicators is evident in its people awareness, security portals, food availability, security, and innovation. Keywords: corona virus, evaluation, Kampung Tangguh (Resilient Kampong)